DESAIN RAK DISPLAY UNTUK PENERBIT ZIFATAMA - Omar Mukhtar; Faza Wahmuda (Indonesian Society of Applied Science, 2021)
The low interest of people in reading has closed several book publishers as their books were not in demand. Furthermore, there are some publishers who sell their books only for private users such as Zifatama book publisher in Sidoarjo. If this publisher wants to put their books at big book shops, it will get very high charge of tax. This fact has underpinned the researcher to design a portable shelf specifically for Zifatama book publisher so that it can sell the books in the interior events such as seminar, workshop, and training. To design the display shelf, the researcher employed mix method by observing various places related to display shelves and interviewing the head of Zifatama publisher. Those methods aimed to ease the researcher in developing the product through some analyses regarding the needs, activity, display product types, product placement, design style, shape, system, color, technology of information media, material, ergonomics, and product dimension. The final result obtains a product of display shelf having design concepts of informative and modern minimalist which is stackable to ease the publisher bringing it during an interior event. In addition, this display shelf presents information on Zifatama Publisher books to users.